On controllability problems for the wave equation on a half-plane - Fardigola, L. V. (Журнал математичної фізики, аналізу, геометрії, 2005)
Necessary and sufficient conditions for null-controllability and approximate null-controllability are obtained for the wave equation on a half-plane. Controls solving these problems are found explicitly. Moreover bang-bang controls solving the approximate null-controllability problem are constructed with the aid of the Markov power moment problem. Mathematics Subject Classification: 93B05, 35B37, 35L05.